Controlling Coxiella burnetii in naturally infected sheep, goats and cows, and public health implications: a scoping review - Toledo-Perona, Raquel; Contreras, Antonio; Gomis, Jesús; Quereda, Juan José; García-Galán, Ana; Sánchez, Antonio; Gómez-Martín, Ángel (Frontiers in Veterinary Science, 2024)
Q fever is a worldwide zoonotic disease which domestic ruminants are the main source of infection for humans. This scoping review summarizes the control measures currently available to reduce Coxiella burnetii (Cb) infection in naturally infected sheep, goat and cattle herds. A total of 28 articles were included in the review. A lack of methodological standardization was noted in the articles analysed. The results indicated that long-term vaccination in cows reduces bacterial excretion in milk and environmental contamination. In small ruminants, the results of vaccination in terms of efficacy are variable. In goats, there is a reduction in bacterial excretion, unlike in sheep, where a long-term vaccination program is necessary to reduce bacterial excretion. Moreover, the high persistence of viable Cb in the environment means that control measures for sheep are needed for several years. The use of antibiotics as a control measure in cows and sheep was not found to reduce excretion. However, the combination of vaccination with antibiotic therapy appears to have positive effects in small ruminants in terms of controlling outbreaks of Q fever. Hygiene and biosecurity measures are the basic means for controlling Cb infection on ruminant farms and ensuring public health.